2021
DOI: 10.21203/rs.3.rs-46998/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early detection of osteoarthritis in the rat with an antibody specific to type II collagen modified by reactive oxygen species

Abstract: Background: Osteoarthritis (OA) is a disease of the whole joint, with articular cartilage breakdown as a major characteristic. Cartilage degradation is mostly driven by chondrocytes which produce inflammatory mediators, proteases and oxidants. Nevertheless, the early pathogenesis events are still unclear. We employed antibody that is specific to oxidative post-translationally modified collagen type II (anti-oxPTM-CII) to detect early cartilage pathogenic changes in two rat models of OA. Methods: The animals un… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In the present study, a typical joint broadening symptom was observed after DMM surgery that peaked during week 1, persisted until the end of the study, and was sensitive to anti-inflammatory Zilretta treatment. Joint broadening can potentially be a consequence of surgery, synovitis, bone remodeling or another pathology [16,20]. The effect has been shown to be exaggerated when rats are housed in RCCs compared with type IV cages [15].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, a typical joint broadening symptom was observed after DMM surgery that peaked during week 1, persisted until the end of the study, and was sensitive to anti-inflammatory Zilretta treatment. Joint broadening can potentially be a consequence of surgery, synovitis, bone remodeling or another pathology [16,20]. The effect has been shown to be exaggerated when rats are housed in RCCs compared with type IV cages [15].…”
Section: Discussionmentioning
confidence: 99%